The urban green carbon index (UGCI): A spatial framework for suggesting urban carbon management - Inhye Seo; Junge Hyun; Bokyung Son; Yeonsu Lee; Jungho Im; Jongho Kim; Sujong Jeong; Gayoung Yoo (PLoS ONE, 2026)
Enhancing carbon (C) sequestration in urban green spaces is essential for urban carbon neutrality; yet the spatial heterogeneity and structural complexity of urban landscapes hinder the development of targeted, actionable management strategies. This study introduces a decision-support framework that integrates a novel Urban Green Carbon Index (UGCI) with a multi-dimensional analytical approach for assessing and guiding urban C management. The UGCI combines 30 m-resolution spatial data on vegetation C storage, soil C storage, net C uptake, and soil C storage potential, and identifies the three most influential components based on the weights derived from their spatial variability. The multi-dimensional approach depicts the relative importance among the three core UGCI components, thereby enabling site-specific and component-focused management directions. A case study in Suwon, South Korea, showed that the UGCI captured pronounced within-patch heterogeneity, recording 21–45% lower values at edges compared with interiors, thereby identifying specific locations within green patches where localized management to improve C conditions is most warranted. Based on the limited components revealed by the ternary analysis, tailored management practices, such as surface litter retention, soil decompaction, and multi-layered planting, were proposed to improve the weaker C components. This framework provides a scientifically grounded and policy-ready basis for spatially explicit diagnosis and management of urban C, supporting a transition from generalized greening efforts toward quantifiable, site-specific C enhancement strategies.